Конструктивные признаки жилых построек и их типология на поселениях Степного Среднедонечья VIII - нач.Х в. - Красильникова, Л.И. (Степи Европы в эпоху средневековья, 2001)
The archaeological sites of the Seversky Donets basin belong to the steppe variant of the Sal to v - Mayatsky cultere. The investigation of constructions, and dwellings in particular, is an important part of archaeological research carried out here. 90 construction units have been cleared out on the sites, 50 of them being dwellings. According to their design the dwelling were divided into three groups: complex constructions making up a separate group. Typologically the dwellings were subdivided according to 7 main parameters constituted by 34 traits. All types of dwellings were attributed as belonging to Protobulgarians who had lived in compact communities in the Donets river steppes. The dwelling design transformation from round yurta-like constructions into square -type 2, and rectangular - type 3, semi-dugouts was caused by two main factors: l)a general trend of the economic development towards settled life with farming, cattle-raising and handicraft manufacturing; 2) hard climate and natural conditions of the steppe zone that made people’s life extremely difficult. The influence of the neighbouring ethnic groups (the Slavs, the Alans and others) should not be underestimated either. We have determined in general the following data concerning the dwellings of the Vlllth - early Xth cc.: the chronological limits of the dwelling design evolution, the sequence of the evolution stages, the main constructive elements of the dwellings, the sets of household appliances within them, their layouts, and the causes of their destruction.